Diameter and dissection of the abdominal aorta and the risk of distal aortic reoperation after surgery for type A aortic dissection - Biancari, Fausto; Perrotti, Andrea; Juvonen, Tatu; Mariscalco, Giovanni; Pettinari, Matteo; Lega, Javier Rodriguez; Di Perna, Dario; Mäkikallio, Timo; Onorati, Francesco; Wisniewki, Konrad; Demal, Till; Pol, Marek; et al. (International journal of cardiology, 2024)
BACKGROUND: Surgery for Stanford type A aortic dissection (TAAD) is associated with an increased risk of late aortic reoperations due to degeneration of the dissected aorta. METHODS: The subjects of this analysis were 990 TAAD patients who survived surgery for acute TAAD and had complete data on the diameter and dissection status of all aortic segments. RESULTS: After a mean follow-up of 4.2 ± 3.6 years, 60 patients underwent 85 distal aortic reoperations. Ten-year cumulative incidence of distal aortic reoperation was 9.6%. Multivariable competing risk analysis showed that the maximum preoperative diameter of the abdominal aorta (SHR 1.041, 95%CI 1.008-1.075), abdominal aorta dissection (SHR 2.133, 95%CI 1.156-3.937) and genetic syndromes (SHR 2.840, 95%CI 1.001-8.060) were independent predictors of distal aortic reoperation. Patients with a maximum diameter of the abdominal aorta >30 mm and/or abdominal aortic dissection had a cumulative incidence of 10-year distal aortic reoperation of 12.0% compared to 5.7% in those without these risk factors (adjusted SHR 2.076, 95%CI 1.062-4.060). CONCLUSION: TAAD patients with genetic syndromes, and increased size and dissection of the abdominal aorta have an increased the risk of distal aortic reoperations. A policy of extensive surgical or hybrid primary aortic repair, completion endovascular procedures for aortic remodeling and tight surveillance may be justified in these patients. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT04831073.
Keywords: aortální aneurysma; Deoxyglucose; Diameter; Aortic Dissection; deoxyglukosa; cévy - implantace protéz; výsledek terapie; aneurysma hrudní aorty; lidé; disekce aorty; Loeys-Dietz syndrome; Treatment Outcome; Reoperation; Aortic Aneurysm, Thoracic; Risk Factors; reoperace; retrospektivní studie; Genetic syndrome; Azides; azidy; Vascular Ehlers-Danlos syndrome; aorta abdominalis; rizikové faktory; Size; Blood Vessel Prosthesis Implantation; Aortic dissection; Retrospective Studies; Marfan syndrome; Aorta, Abdominal; Aortic Aneurysm; Type A aortic dissection; Humans